1976
DOI: 10.1139/p76-159
|View full text |Cite
|
Sign up to set email alerts
|

The electronic spectrum of F2

Abstract: The absorption spectrum of F2 in the 780–1020 Å range has been photographed at sufficient resolution to allow a rotational analysis of many bands. A large number of vibrational levels of three ionic states have been observed and their rotational constants determined. Many perturbations in the rotational structure caused by the interaction between the three states have been investigated and the interaction energies determined. The rotational and vibrational structures of a few Rydberg states have also been anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(63 citation statements)
references
References 0 publications
6
55
1
1
Order By: Relevance
“…The vibration rotation spectrum had been measured in 1976 at the Herzberg Institute in Ottawa by means of highresolution electronic spectroscopy. 95 The mean absolute deviation between the 22 experimentally observed and our ab initio calculated levels turns out to be 5 -6 cm −1 . We are using the conversion factor: 1 mhartree ϵ 219.4746 cm −1 .…”
Section: Introductionmentioning
confidence: 64%
“…The vibration rotation spectrum had been measured in 1976 at the Herzberg Institute in Ottawa by means of highresolution electronic spectroscopy. 95 The mean absolute deviation between the 22 experimentally observed and our ab initio calculated levels turns out to be 5 -6 cm −1 . We are using the conversion factor: 1 mhartree ϵ 219.4746 cm −1 .…”
Section: Introductionmentioning
confidence: 64%
“…145 From the resulting fully ab initio potential energy curve of F 2 , the vibrational and rotational energy levels will then be calculated and compared with the experimentally determined spectrum. 109 The accuracy of CEEIS method can be pushed further by taking into account larger CI expansions. This would also call, however, for the use of larger basis sets and the possible accounting of smaller physical corrections such as nonadiabatic effects or spin-spin couplings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we calculate the potential energy curve for the dissociation of the F 2 molecule into two F atoms. Its rovibrational ground state spectrum has been accurately determined by experiment, 108,109 which allows the critical assessment of the theoretical results in all regions of the dissociation curve. While there exist numerous investigations of the nearequilibrium properties [110][111][112][113][114][115][116][117][118] and some theoretical studies of the dissociation curve, 66,68,69,71,[119][120][121][122][123][124][125][126][127][128][129] the latter has proven to be a difficult case due to the weakness of its chemical bond.…”
Section: Introductionmentioning
confidence: 99%
“…The range corresponds to the typical sextupled output of a pulsed dye laser, in this case with a mixture of rhodamine 590 and rhodamine 610, while scanning over its gain profile. The spectrum consists of a vibrational progression of red-shaded bands to the C 'Cz valence state in the notation of Colbourn et al [4]. The vibrational numbering is not yet established and is therefore given with an arbitrary offset n. The transition to the C 'Es, v= n A-26 state is strongest and individual spectral lines are recorded with a signal-to-noise ratio of up to 1000.…”
Section: Spectroscopymentioning
confidence: 99%
“…Investigations of the discrete absorption spectrum started in 1959 [ 31. The most detailed and accurate study of the extreme ultraviolet (XUV) absorption spectrum was reported by Colbourn et al [4]. In the wavelength range between 95 and 102 nm they observed several vibrational progressions, the most intense being denoted as the C '1: state.…”
Section: Introductionmentioning
confidence: 99%